Efficiency of Saving and Credit Cooperative Units in North Aceh, Indonesia - Ghazali Syamni; M Shabri Abd Majid (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2016)
The purpose of this study is to measure and analyze the relative efficiency of saving and credit cooperative units in North Aceh, Indonesia. In this study, the selection of inputs and outputs to be analyzed by the Data Envelopment Analysis (DEA) was selected using the intermediation approach. The results showed that the overall saving and credit cooperative units in North Aceh, Indonesia have not operated fully efficient. This is indicated by the average of value of Malmquist Productivity Index which was still below one, but individually the study found that some cooperatives have operated efficiently, such as cooperative employee of PT Pupuk Iskandar Muda (Persero), KPN Kopebun, KPN Citra Guru, KPN Tunas and Kopbun Cut Mutia. These findings implied that more serious efforts should be made by the saving and credit cooperative units in North Aceh, Indonesia to improve the cooperative management efficiency levels by managing their capital and assets professionally. DOI: 10.15408/sjie.v5i2.3193